Efficacy of laparoscopic radical resection of right-sided colon cancer by different surgical approaches: network-meta-analysis - Li, Mingyi; Hu, Jie; Suo, Liwei; Wu, Hui; Li, Ziming; Xu, Xiaoyi; Zhang, Shifeng (BMC surgery, 2024)
There are a growing number of surgical approaches for laparoscopic radical resection of right-sided colon cancer, while there are relatively few comparative analyses of the different surgical approaches. To evaluate the safety and efficacy of different surgical approaches (intermediate approach, caudolateral approach, caudolateral combined with intermediate approach) for laparoscopic radical resection of right-sided colon cancer by conducting a network meta-analysis (NMA). We searched PubMed, Web of science and China National Knowledge Infrastructure (CNKI) databases. We reviewed the Chinese and English literature on controlled studies of laparoscopic radical resection of right-sided colon cancer including intermediate approach, caudolateral approach and caudolateral combined with intermediate approach, reported from the establishment of the database to September 2023. The inclusion and exclusion criteria were independently conducted by two researchers and relevant data was extracted from the qualifying literature and analyzed using Stata15 software. Nine controlled studies of relevance including 715 patients were screened with right-sided colon cancer. Net meta-analysis showed that compared with the intermediate approach, the caudolateral approach was superior to the intermediate approach in terms of operation time (SMD = 0.75, 95% CI = 0.38 ~ 1.12, P = 0.0001), and bleeding volume (SMD = 1.15, 95% CI = 0.18 ~ 2.13, P = 0.002), while the difference was not statistically significant among the caudolateral approach compared with the intermediate approach in terms of the number of lymph node dissection, postoperative complication rate, time to first postoperative flatus and postoperative hospitalization. Compared with the intermediate approach, the combined approach was superior to the intermediate approach in terms of operation time (SMD = -0.87, 95% CI = -1.22 ~ -1.52, P < 0.05), bleeding volume (SMD = -1.09, 95% CI = -1.98 ~ -0.19, P < 0.05), the number of lymph node dissection (SMD = 0.21, 95% CI = 0.01 ~ 0.41, P < 0.05), and postoperative complication rate (RR = 2.24, 95% CI = 1.21 ~ 4.13, P < 0.05), while the difference was no statistically significant among the combined approach compared with the intermediate approach in terms of time to first postoperative flatus and postoperative hospitalization. Compared with the caudolateral approach, there was no statistically significant difference between the caudolateral approach and the combined approach in terms of operation time, bleeding volume, the number of lymph node dissection, postoperative complication rate, time to first postoperative flatus and postoperative hospitalization. According to the results of the surface under the cumulative ranking curve (SUCRA), the caudolateral approach and the combined approach were superior to the intermediate approach in terms of operation time (SUCRA: 65.1%, 84.9%, 0), bleeding volume (SUCRA: 77%, 71.9%, 1%), the number of lymph node dissection (SUCRA: 49.6%, 90.8%, 9.7%), postoperative complication rate (SUCRA: 46.6%, 97.5%, 5.9%), time to first postoperative flatus (SUCRA: 67%, 77.8%, 5.2%), postoperative hospitalization (SUCRA: 30.8%, 96.4%, 22.8%). The caudolateral combined with intermediate approach and the caudolateral approach are safer and more effective than the intermediate approach. According to the results of SUCRA, the combined approach is superior to the caudolateral approach in terms of operation time, the number of lymph node dissection, postoperative complication rate, time to first postoperative flatus and postoperative hospitalization, the caudolateral approach is superior to the combined approach in term of bleeding volume.